Four new dendrochirotid holothurians collected from the Seto Inland Sea and the western part of the Sea of Japan, western Japan - Yamana, Yusuke; Nakaguchi, Kazumitsu; Yamaguchi, Shuhei; Katoh, Mikio; Ogawa, Akito; Ohtsuka, Susumu (Zootaxa, 2021)
Fifteen dendrochirotid holothurians, including four new species, were collected from the Seto Inland Sea and the western part of the Sea of Japan, western Japan by the training and research vessel (TR/V) TOYOSHIO MARU of Hiroshima University, during the 2014–15 surveys. Massinium toyoshiomaruae sp. nov., Thyone kyushuensis sp. nov., T. liaoi sp. nov., and T. toyoshiomaruae sp. nov. are described as new species. Massinium toyoshiomaruae sp. nov. is readily distinguishable from all congeners by the absence of bodywall ossicles and the presence of table ossicles in the tentacle base. Thyone kyushuensis sp. nov. possesses large polyporous-tables in the introvert and tentacles, bodywall ossicles of a peculiar shape, and tentacle ossicles comprised mostly of unbranching rods and/or rod-like rosettes, which differ from those of all congeners. Thyone liaoi sp. nov. resembles T. pedata Semper, 1867 in its bodywall ossicles, however, it is distinguishable by the absences of huge ossicles in the body wall and the needle-shaped ossicles in the gonadal tubules. Thyone toyoshiomaruae sp. nov. is distinguishable from all other Thyone by the presence of the peculiar shape of the bodywall ossicles. Partial sequences of the mitochondrial cytochrome c oxidase subunit I gene are provided from the type specimens of the new species as DNA barcoding data.